L’incertitude dans l’utilisation des médias géolocalisés : étude de deux applications reliées à la mobilité urbaine - Julia Salles (Netcom)
Drawing from the differentiation between strategic and tactical practices, developed by Michel de Certeau (1990), and the concept of hybrid space (De Souza e Silva, 2006; Nova, 2009), this paper aims to distinguish the various relationships to uncertainty in the context of location-based mobile applications forurban mobility, through the study of two mobile applications, Foursquare/Swarm and Walking the Edit.